DIAGNOSTIC APPROACHES FOR MACULAR DYSTROPHY BY USING OCT AND VEP : A CASE SERIES - Saldianovitta, Rahajeng Anugrahing; Dewi, Nadia Artha (Indonesian Vitreoretinal Society, 2024)
Introduction: Macular dystrophies (MDs) consist of a heterogeneous group of disorders that are characterized by bilateral symmetrical central visual loss. Clinical manifestation including atrophy in macula. This cases series provides clinical manifestation and characteristics in ancillary testing for better approach to macular disease Case report: Case 1 is 13-year-old girl with decrease visual acuity, uncorrected visual acuity (UCVA) was 2/60 on both eyes. The ophthalmologic examination showed an area of atrophy at macula accompanied with yellowish flecks on both eyes. Optical coherence tomography (OCT) shows thinning in all areas of macula and loss of outer nuclear layer (ONL) and photoreceptor. From VEP, there were low amplitude N75, P100, and N145 waves without any latency. Case 2 is 39-year-old woman with decrease of visual acuity, UCVA was 6/60 on both eyes, accompanied with partial colour blindness and red-green deficiencies. From ophthalmology examination showed large atrophy area at macula. OCT examination shows thinning in most of macula area and decrease of ONL thickness and photoreceptor. VEP showed normal wave without any latency. Discussion: There were a gradual central vision loss, at a more advanced stage, color blindness can occur due to photoreceptor damage in the macular area. From the posterior segment there was a yellowish spot on the macula which suggested lipofuscin deposition on the retinal pigment epithelium (RPE). From OCT, there ware loss of ONL and VEP showed low amplitude or normal waves. This findings suggested macular dystrophy due to Stargardt disease. Conclusion: OCT and VEP can be used to detect anatomical and physiological abnormalities that can aid in the diagnosis of macular dystrophy in the case of incomplete ancillary testing tools.